Precision nutrient management in maize (Zea mays) for higher productivity and profitability - S, SHYAM C; RATHORE, S S; SHEKHAWAT, KAPILA; SINGH, R K; PADHAN, SMRUTI R; SINGH, V K (The Indian Journal of Agricultural Sciences, 2021)
An agronomic field experiment on "Precision nutrient management in maize (Zea mays L.) for higher productivity and profitability through Decision Support Tools" was conducted at ICAR-IARI New Delhi, India during kharif 2018. The objective was to enhance seed yield and economics of maize crop trough precision nutrient management. The growth (plant height, dry matter, leaf area, leaf area index), and yield attributes and seed yield were improved under precision nutrient management practices of NE+GS7T, NE6T, NE7T, and NE+GS 6T. The maximum LAR was observed with NE+GS7T at 60 DAS. Maximum cob length was 15.92 cm under NE7T. Plant height was maximum under NE7T (192.5 cm) and NE+GS7T (191.3 cm), similarly maximum dry matter accumulation was in NE7T, which was >22.0% over state recommendation at harvesting stage of maize crop. Grain yield, total biomass of maize was also the highest under NE7T nutrient management (6.2 t/ha). Maximum net return was in NE7T (` 75194/ ha) and least were in N omission (` 12992 to 20451/ha).